The Progress of Immunotherapy in Refractory Pituitary Adenomas and Pituitary Carcinomas - Dai, Congxin; Liang, Siyu; Sun, Bowen; Kang, Jun (Frontiers in Endocrinology, 2020)
Most pituitary adenomas (PAs) are considered benign tumors, but approximately 0.2% can present metastasis and are classified as pituitary carcinomas (PCs). Refractory PAs lie between benign adenomas and true malignant PC and are defined as aggressive-invasive PAs characterized by a high Ki-67 index, rapid growth, frequent recurrence, and resistance to conventional treatments, including temozolomide. It is notoriously difficult to manage refractory PAs and PC because of the limited therapeutic options. As a promising therapeutic approach, cancer immunotherapy has been experimentally used for the treatment of many tumors, including pituitary tumors. The purpose of this review is to report the progress of immunotherapy in pituitary tumors, including refractory PAs and PCs. The tumor immune microenvironment has been recognized as a key contributor to tumorigenesis, progression, and prognosis. One study indicated that the number of CD68+ macrophages was positively correlated with tumor size and Knosp classification grade for tumor invasiveness. The infiltration of CD4+ and CD8+ T cells was relatively scant in these adenomas, but pituitary growth hormone (GH) adenomas exhibited significantly more CD4+ and CD8+ T cells than non-GH adenomas. These results suggest an association of CD68+ macrophage infiltration with an increase in pituitary tumor size and invasiveness.Preclinical studies have indicated that widely varying degrees of programmed death-ligand 1 (PD-L1) expression and tumor-infiltrating lymphocytes (TILs) are found among different subtypes. Clinical studies show that immunotherapy may be an effective treatment in patients with pituitary tumors. One corticotroph carcinoma patient showed a significant reduction in hormone levels and shrinkage of the tumor size of primary and metastatic lesions immediately after investigational treatment with ipilimumab and nivolumab. However, another patient with corticotroph adenoma progressed rapidly after four cycles of anti-PD-1 (pembrolizumab) treatment. In summary, the results from preclinical research and clinical studies indicated that immunotherapy might be a promising alternative therapy for PCs and refractory PAs resistant to conventional treatments. The combination of immunotherapy and radiotherapy or temozolomide may have synergistic effects compared to a single treatment. More preclinical and clinical studies are needed to further indicate the exact efficacy of immunotherapy in pituitary tumors.